PENGARUH TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL - Anna Lasturi Sinaga; Sudarno Sudarno (Diponegoro Journal of Accounting, 2018)
The aims of this study is to examine the effect of corporate governance, such as family ownership, foreign ownership, Independent Directors, CEO duality, family duality, and number of Audit Committee meetings on intellectual capital disclosure. This study uses firm size, firm age, and return on assets as control variables. The population of this study are all of listed firms in Indonesia Stock Exchange in 2014, 2015, and 2015. The sampling method in this study is purposive sampling. The company used must have complete data on the implementation of corporate governance, so that in this study there were 204 years-firms-observation. Data analyzed with test of classic assumption and examination of hypothesis with multiple linear regression method. Result of this research indicates that family ownership, foreign ownership, CEO duality and number of Audit Committee meetings have positive and significant effect to intellectual capital disclosure in Indonesia. While the factor of family duality, and Independent Directors factor have not significant effect to intellectual capital disclosure in Indonesia.